Modelling & docking studies of wild and mutant Rubisco enzyme in dunaleilasalina - INAMUL HASAN MADAR; PRIYADARSHAN KATHIRVEL; SUDHA SUBRAMANIAN; HUSSAIN AL SSADH; ASHVINI DESAI; IFTIKHAR ASLAM TAYUBI; AMJAD HUSSAIN.A; S.K.M. HABEEB (International Journal of Pharma and Bio Sciences, 2017)
Rubisco is an important enzyme in photosynthesis as well as photorespiration. Rubisco plays dual role of carboxylation and oxygenation and the type of reaction is determined by specific amino acids at the active site. The carbon fixation has been shown to be favored by the involvement of Lys-334 of Rubisco with enediol of RuBP. The role of lysine at position 334 of loop 6 of Rubisco has been experimentally studied in many species. In the present study, we attempted to predict the change encountered during modification of the amino acid Lys-334 in the active site of D. salina Rubisco. For this, we had modelled the wild type and mutant structure of Rubisco enzyme from Dunaliella salina with MODELLER 9v3 and evaluated the model using Procheck3.5.4. The modelled structure was then docked using Autodock with CABP, the substrate analogue of RuBP as Lys-334 at the apex of the loop has iconic interaction with it. The dock score of wild type and mutant type were -9.26 and -7.91 respectively. The result of algorithmic predictions of observed differences in the binding affinities of wild type and mutant structure of Rubisco. As our results also predicted the importance of Lys-334 in Rubisco of D. salina.